Efeitos da terapia laser de baixa intensidade e de membranas de celulose bacteriana no tratamento de queimaduras de terceiro grau em ratos - Brassolatti, Patricia (2015)
Burn injuries represent a high risk of morbidity and mortality worldwide. In severe and deep injuries, the wound healing process is complex and requires the participation of different types of cells. Among the existing treatments, biomaterials and LLLT are highlighted for having properties that favor and stimulate the healing process. Thus, three studies were conducted to evaluate the effects of bacterial cellulose membranes in its pure state or enriched with lidocaine and LLLT (660 nm) in two different fluences (12.5J/cm2 and 25J/cm2) used independently or associated, on third-degree burns in rats. The burn was induced with an aluminum plate at 150°C, pressed onto the animal's back for 10 seconds. In the first study the action of bacterial cellulose membrane in its pure state and enriched with lidocaine, as biological dressings was evaluated. Therefore, the rats were divided in three experimental groups, CG (control group), MG (group treated with the pure bacterial cellulose membrane), and MLG (group treated with the bacterial cellulose membrane with lidocaine). The treated groups showed an advanced wound healing when compared to the control group. In the immunohystochemical analysis of COX-2, the treated groups showed a light immunoexpression, with the characteristics of repaired tissue. Thus, bacterial cellulose-based biological dressings were effective and provided a favorable environment for the development of the healing process. In the second study, the effects of LLLT with two different fluences (12.5J/cm2 and 25J/cm2) in three experimental groups, divided into CG (control group), LG12.5 (burning treated group 12.5 J/cm2) and LG25 (burn group treated with 25 J/cm2) were evaluated. The animals received laser application immediately after the induction of the lesion and the subsequent doses 2, 4, 6 and 8 days after the induction, at five different points, four on the edges of the wound and one in the central region. The LG25 had better results, with higher number of blood vessels, increased immunoexpression of VEGF (Vascular Endothelial Growth Factor) and decreased immunoexpression of COX-2 (Cyclooxygenase-2) when compared to CG and GL12.5 groups. The LG12.5 showed the longest delay in the progression of the healing process, due to its intense inflammation and tissue fibrosis when compared to CG and LG25. In the third study the association of pure bacterial cellulose membrane and LLLT (660 nm, 25 J/cm2) was investigated. Four groups were evaluated, CG (control group), MG (burn group treated with pure bacterial cellulose membrane), LG (burn group treated with laser 25 J/cm2) and MG + L (burn group treated with bacterial cellulose membrane + LLLT). Histological findings demonstrated that the treated group showed better results in the healing process. The (GM + L) showed results similar to those found in the GL, evidencing the stimulatory effects of angiogenesis provided by the laser light. GM showed improvement in the healing process, indicating the proliferative phase. However, although LLLT presented the expected proinflam matory effects, which modulate the inflammatory phase and favor tissue regeneration, the isolated action of the bacterial cellulose membrane proved to be advantageous by presenting tissue characteristics, which are compatible with a more advanced phase of the healing process.